Determinants of households' food diversity demand in Uganda - Tankari, Mahamadou Roufahi; Badiane, Ousmane (International Association of Agricultural Economists, 2015)
Given that a diversified food contributes to the individuals' health reinforcement, this analysis has tried to identify the households' food diversity demand determinants in Uganda by using a latent class model. Its implementation reveals several important results. Beyond the traditional determinant (income), on the one hand, one can note that the characteristics of the household influence the food diversity demand with a variable intensity according to the class considered. On the other hand, it appears that the structure of the household is a significant factor determining the food diversity demand. Besides, there is also an area of residence impact on food diversity demand. Consequently, the consideration of this heterogeneity of the population in the formulation of nutritional policies is necessary in order to make those more efficient by targeting households, empowering women, facilitation access to markets or encouraging a diversified agricultural production. Tankari, Mahamadou Roufahi; Badiane, Ousmane